Dress like a woman : working women and what they wore - Gay, Roxane; Friedman, Vanessa; Massey, Sarah; Albert, Ashley; Jacobs, Emma (New York : Abrams Image, 2018)
"What does it mean to dress like a woman? Today, a woman can be a surgeon, an artist, an astronaut, a mlitary officer, an athlete, a judge, a scientist--the possibilities are endless. The photographs inside this book depict women-- both familiar and unknown-- who inhabit a fascinating intersection of fashion, gender, class, nationality, and race, proving there is no single answer to this question .... Dress Like a Woman is a comprehensive look at the role of gender and clothing in the workplace"--Back cover.
"Editors: Sarah Massey, Ashley Albert, and Emma Jacobs"--Page [2].
Keywords: Women's clothing -- History -- Pictorial works; Women employees -- Clothing -- History -- Pictorial works; Women -- Employment -- History -- Pictorial works; Women's clothing -- History; Women's clothing -- Social aspects; Women -- Employment -- History